Portuguese colonialism and Angolan resistance in the memoirs of Adriano João Sebastião (1923‐1960) (Revista Tempo e Argumento, 2017)
This article discusses the greater presence ofPortuguese colonialism in the Angolan countrysidein the first half of the 20th century and theresistance to it. To do this, we follow a part of thelife of the politician Adriano João Sebastião fromhis birth, in 1923, to his arrest, in 1960, through theanalysis of his memoir book Dos campos dealgodão aos dias de hoje [From the cotton fields tothe present day], published in 1993. Thus, we aimto grasp how Portuguese colonialism affected thedaily life of an Angolan man.Keywords: Angola; Colonization; Resistance;Adriano Sebastião; Memoirs.